Arterial Load and Norepinephrine Are Associated With the Response of the Cardiovascular System to Fluid Expansion - Nguyen, Maxime; Mallat, Jihad; Marc, Julien; Abou-Arab, Osama; Bouhemad, Bélaïd; Guinot, Pierre-Grégoire (Frontiers in Physiology, 2021)
Background Fluid responsiveness has been extensively studied through the preload prism. Arterial load might be a factor modulating fluid responsiveness. Norepinephrine administration increase arterial load and modify the vascular properties. The objective of the present study was to determine the relationship between fluid responsiveness, preload, arterial load, and norepinephrine use. We hypothesized that as preload, arterial load and norepinephrine use may affect fluid responsiveness. Methods Retrospective analysis multicentred analysis of pooled data from 446 patients monitored with transpulmonary thermodilution before and after fluid expansion. Fluid expansion was standardized between intensive care units. Comparison of patient with and without norepinephrine at the time of fluid infusion. Stroke volume responsiveness was defined as an increase of more than 15% of stroke volume following fluid expansion. Pressure responsiveness was defined as an increase of more than 15% of mean arterial pressure following fluid expansion. Arterial elastance was use as a surrogate for arterial load. Results 244 patients were treated with norepinephrine and 202 were not. By univariate analysis, arterial elastance was correlated to stroke volume variations with fluid expansion. However, stroke volume variations was not associated to norepinephrine administration (26 [15;46] % vs 23 [10;37] %, p=0.12). By multivariate analysis, high arterial load and norepinephrine administration were associated with fluid responsiveness. The association between arterial elastance and fluid responsiveness was less important in patient treated with norepinephrine. Whereas arterial compliance increased in absence of norepinephrine, arterial compliance did not change in patient treated with norepinephrine (6 [-8;19] % vs 0 [-13;15] %, p = 0.03). Total peripheral and arterial elastance changes were less important in patients with norepinephrine (- 8% [-17;1] vs -11% [-20;0] p < 0.05 and -10 % [-19;0] vs -16 % [-24;0], p = 0.01). Conclusions Arterial load and norepinephrine administration were associated with fluid responsiveness. High arterial load was associated with fluid responsiveness. In patient treated with norepinephrine, this association was lower and the changes of arterial load following fluid expansion seemed mainly driven by its resistive component.